ANALISIS PENGUJIAN STRUKTUR BALOK LAMINASI KAYU SENGON DAN KAYU KELAPA - Handayani, Sri (Jurnal Teknik Sipil dan Perencanaan, 2016)
Wood Sengon (Sengon) is a type of timber that can quickly grow, accessible but its use as a construction material has not been optimized. The technology used to support the wood as a construction material is a laminate. Engineering experiments was done by making laminated beams of wood Sengon and wood coconut. The purpose of this study is to determine how much the increase in flexural strength for laminated wood Sengon beams and wood Coconut beams as a replacement of structural beam with a variety of adhesive and timber placement. The method used is an experimental method for flexural strength testing of laminated beams. The results showed an average flexural strength of the maximum obtained in laminated beams with variations EP-S (adhesive epoxy glue and placement position in the wood Sengon) amounted to 679 350 kg / cm2. An increase in the strength of 254 025 kg / cm2 (59.72%) are from wood Sengon bending strength 425 325 kg / cm2 (probe grade IV) to 679 350 kg / cm2 (strong class III). The use of technology should pay attention to the position of the bearing laminated wood. Wood with strong higher class should be put on the outside position to provide reinforcement for the wood with a powerful low grade placed in the position. Kayu Sengon (Sengon) termasuk dalam jenis kayu yang dapat dengan cepat tumbuh, mudah di dapat tetapi penggunaannya sebagai bahan konstruksi belum optimal. Teknologi yang digunakan guna mendukung kayu sebagai bahan konstruksi adalah dengan laminasi.  Rekayasa eksperimen dilakukan dengan membuat balok laminasi dari kayu Sengon dan kayu Kelapa. Tujuan penelitian ini adalah untuk mengetahui seberapa besar peningkatan kuat lentur balok kayu dengan laminasi Sengon dan Kelapa sebagai pengganti balok struktur dengan variasi bahan perekat dan perletakan kayu. Metode penelitian yang digunakan adalah metode eksperimen  untuk pengujian kuat lentur balok  laminasi. Hasil penelitian menunjukkan kuat lentur rata-rata maksimum  diperoleh pada balok laminasi dengan variasi EP-S  (perekat lem epoksi dan perletakan posisi kayu  Sengon didalam) sebesar 679.350 kg/cm2. Terjadi peningkatan kekuatan sebesar 254.025 kg/cm2 (59.72%) yaitu dari kuat lentur  kayu  Sengon 425.325 kg/cm2 (kelas kuar IV) menjadi 679.350 kg/cm2(kelas kuat III). Penggunaan teknologi laminasi hendaknya memperhatikan posisi perletakan kayu.  Kayu dengan klas kuat lebih tinggi  diletakkan pada posisi luar untuk memberikan perkuatan pada kayu dengan kelas kuat rendah yang terletak pada posisi dalam.